The Impact of Market Attractiveness and Resource Uniqueness in Influence Marketing Performance Through Market Strategy - Anang Martoyo; Sucherly Sucherly; Undang Juju (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Micro businesses make a big contribution to national development, especially in opening up job opportunities so that they can support government programs in reducing unemployment and poverty, but in the last five years the level of marketing performance has fluctuated and tends to slow down. The research aims to examine the ability of micro business actors to implement market strategies to improve marketing performance and business scale.The research used an explanatory survey method with an analysis unit for micro business actors in the DKI Jakarta area with a sample size of 400 respondents. Research data sources include primary and secondary data sources with data collection through observation, literature study, interviews and cross-sectional questionnaires. The analysis technique uses SEM analysis with the LISREL 8.8 programThe results of the research show that market attractiveness and resource uniqueness simultaneously have a significant effect on market strategy with a total influence of 92%, partial market attractiveness has a significant effect on market strategy of 38.6%, while resource uniqueness partially has a significant effect on market strategy by 50.3%. Changes in technology and human resources make a dominant contribution in influencing the effectiveness of implementing market strategies. Market strategy has a significant influence on marketing performance with a total influence of 94%. Positioning provides the most dominant contribution in influencing marketing performance.Recommendations for micro business actors in formulating market strategies to consider aspects of technological change and human resource competence to achieve more optimal marketing performance improvements.